2021
DOI: 10.3389/fpsyg.2021.729083
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Class and Generalized Trust: The Mediating Role of Sense of Control

Abstract: The success and well-being theory of trust holds that higher social class is associated with higher generalized trust, and this association has been well documented in empirical research. However, few studies have examined the processes that might explain this link. This study extends this assumption to explore the mediating mechanism in the association. We hypothesized that social class would positively predict generalized trust, and the relationship would be mediated by people’s sense of control. Self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Consistent with the foregoing theorized impact of low SES on perceived control, numerous studies have confirmed that SES is positively associated with perceptions of control in general, within specific domains, and across daily experiences (e.g., Gallo et al., 2005; Johnson & Krueger, 2006; Kraus et al., 2009; Lachman & Weaver, 1998; Qiang et al., 2021). SES also predicts a tendency to make internal and controllable attributions for outcomes (Daganzo & Bernardo, 2018; Kraus et al., 2009).…”
Section: Low Ses and Reduced Perceptions Of Controlmentioning
confidence: 65%
“…Consistent with the foregoing theorized impact of low SES on perceived control, numerous studies have confirmed that SES is positively associated with perceptions of control in general, within specific domains, and across daily experiences (e.g., Gallo et al., 2005; Johnson & Krueger, 2006; Kraus et al., 2009; Lachman & Weaver, 1998; Qiang et al., 2021). SES also predicts a tendency to make internal and controllable attributions for outcomes (Daganzo & Bernardo, 2018; Kraus et al., 2009).…”
Section: Low Ses and Reduced Perceptions Of Controlmentioning
confidence: 65%